Community Answer

Honor CodeSolved 1 Answer

See More Answers for FREE

Enhance your learning with StudyX

Receive support from our dedicated community users and experts

See up to 20 answers per week for free

Experience reliable customer service

Get Started

y^{\prime \prime}-8 y^{\prime}+16 y=\frac{-0.5 e^{4 t}}{t^{2}+1}corresponding homogeneous differential equation is, y^{\prime \prime}-8 y^{\prime}+16 y=0 \ldots(2)\therefore The auxillary eqn of (2) is,\begin{array}{l}m^{2}-8 m+16=0 \\\therefore(m-4)^{2}=0 \ldots\left[(a-b)^{2}=a^{2}-2 a b+b^{2}\right] \\\therefore m=4,4 \text { (repeated goots.). } \\\end{array}\therefore General solution of (2) is,y_{h}(t)=c_{1} e^{a t}+c_{2} t e^{4 t}where C_{1} C_{2} are constants f y_{1}=e^{u t}+y_{2}=t e^{u t}.Now, To find the particulor solution of (T), for this we ase the variation of param eter method.Let y_{p}(t)=v_{1} y_{1}+v_{2} y_{2}where v_{1}=-\int \frac{y_{2} \cdot R(t)}{w\left(y_{1} y_{2}\right)} d t, v_{2}=\int \frac{y_{1}-R(t)}{w\left(y_{1} y_{2}\right)} d t.\begin{aligned}W\left(y_{1}, y_{2}\right)=\left|\begin{array}{ll}y_{1} & y_{2} \\y_{1}^{\prime \prime} & y_{2}^{\prime}\end{array}\right| & =\left|\begin{array}{cc}e^{4 t} & t e^{4 t} \\4 e^{4 t} & e^{4 t}+4 t e^{4 t}\end{array}\right| \\& =e^{4 t}\left(e^{4 t}+4 t e^{4 t}\right)-4 t e^{10 t}\end{aligned}\begin{array}{l}\because w\left(y_{1}, y_{2}\right)=e^{8 t}+4 t e^{8 t}-4 t e^{8 t} . \\ =e^{8 t} \\ \epsilon_{R(t)}=\frac{-0.5 e^{4 t}}{t^{2}+1} \\ \therefore v_{1}=-\int \frac{y_{2} \cdot R(t)}{w\left(y_{1}, y_{2}\right)} d t=-\int \frac{t e^{4 t} \cdot\left(-0.5 e^{(t)}\right.}{\left(t^{2}+1\right) e^{g t}} d t . \\ =\int \frac{0.5 t}{t^{2}+1} d t \\ =0.5 \int \frac{t}{t^{2}+1} d t \text {. } \\ =\frac{0.5}{2} \int \frac{2 t}{t^{2}+1} d t \quad\left(\begin{array}{l}\text { divide tmultply } \\ \text { by } 2\end{array}\right) \\ =\frac{0.5}{2} \ln \left(t^{2}+1\right) \quad \cdots\left[\because \int \frac{f^{\prime}(x)}{f(x)} d x=\ln f(x)\right] \\ \therefore v_{1}=\frac{0.5}{2} \ln \left(t^{2}+1\right) \text {. } \\ t v_{2}=\int \frac{y_{1} \cdot R(t)}{w\left(y_{1}, y_{2}\right)} d t=\int \frac{e^{4 t}\left(-0.5 e^{4 t)}\right.}{\left(t^{2}+1\right) e^{8 t}} d t . \\ =-0.5 \int \frac{1}{t^{2}+1} d t \\\end{array}\therefore V_{2}=-0.5 \tan ^{-1}(t)\therefore The parncular solution yp(t) is.\begin{aligned}y_{p}(t) & =y_{2} v_{1}+y_{2} v_{2} . \\& =e^{4 t}\left[\frac{0.5}{2} \ln \left(t^{2}+1\right)\right]+t e^{4 t}\left[-0.5 \tan ^{-1}(t)\right] \\y_{p}(t) & =e^{G t}\left[\frac{0.5}{2} \ln \left(t^{2}+1\right)-0.5 t \tan ^{-1}(t)\right]\end{aligned} ...